2015
DOI: 10.1002/smr.1718
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of distributed Agile software engineering

Abstract: The combination of Agile methods and distributed software development via remote teams represents an emerging approach to address the challenges such as late feedback, slow project timelines, and high cost, typically associated with software development projects. However, when projects are implemented using an Agile model with distributed human resources, there are a number of challenges that need to be considered and mitigated. The objectives of our work are multifold. First, we would like to understand the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 81 publications
1
40
0
Order By: Relevance
“…After removing duplicates, the titles and abstracts of the remaining articles were read. We identified 19 relevant systematic literature reviews in this area ( [4], [6], [7], [9], [17], [20], [21], [22], [23], [33], [34], [35], [36], [37], [38], [39], [40], [41], [42]). By reading the titles of articles that cite these reviews, we identified three more relevant articles ( [18], [43], [44]).…”
Section: Related Workmentioning
confidence: 99%
“…After removing duplicates, the titles and abstracts of the remaining articles were read. We identified 19 relevant systematic literature reviews in this area ( [4], [6], [7], [9], [17], [20], [21], [22], [23], [33], [34], [35], [36], [37], [38], [39], [40], [41], [42]). By reading the titles of articles that cite these reviews, we identified three more relevant articles ( [18], [43], [44]).…”
Section: Related Workmentioning
confidence: 99%
“…Agile based development is by design capable of reducing communication related delays and increasing discussion between software engineers, but it can also reduce the amount of documentation produced [19]. When working in geographically distributed teams, this may introduce challenges in communication since some remote communication, we suggest, may in fact benefit from documented artefacts.…”
Section: Current Role Of a Software Engineermentioning
confidence: 97%
“…Scrum software development is suitable for small projects and it becomes comparatively difficult to follow Scrum in large organizations. One of the main weaknesses of Scrum is reported in [23] that many employees in the software industry lack the knowledge of Scrum. They complete one simple course on Scrum and call themselves as Scrum masters.…”
Section: Related Workmentioning
confidence: 99%